MODERN METHODS OF ANTERIOR CRUCIATE LIGAMENT TENDOPLASTY (LITERATURE REVIEW) - I. N. Mikhaylov; M. E. Puseva; N. V. Tishkov; V. V. Monastyrev; N. S. Ponomarenko; D. B. Balzhinimayev (Acta Biomedica Scientifica)
The first description of surgical treatment of anterior cruciate ligament injuries has become known about a hundred years ago. At the beginning, complete ruptures of the anterior cruciate ligament was treated by open restoration with arthrotomy. At present, open ACL plasty is practically out of use, except for single cases. In recent decades, worldwide, surgical treatment of knee ligament injuries has been performed with arthroscopic techniques. It has long been proven that arthroscopic operations are able to restore the primary anatomy of the damaged joint, combining anatomical validity and minimal traumaticity, pathogenetic justification and high functional efficiency. For more than 50 years, surgeons have been offered many different materials and methods for ACL reconstruction, but nevertheless there is currently no consensus on the choice of rational treatment tactics and the percentage of unsatisfactory results remains significant. Based on the data of modern authors, it can be concluded that the issue of knee joint ligaments damage not only does not lose its relevance, but, on the contrary, due to the increased interest in active lifestyle, it becomes more and more popular and studied. The article presents various views on the basic methods of arthroscopic restoration of the anterior cruciate ligament of the knee joint at the present stage of the development of surgery.